The influence of European MiCa regulation on cryptocurrencies - Conlon, T.; Corbet, S.; Oxley, Leslie (2024)
This research investigates the relationship between impending regulatory measures, specifically the introduction of European MiCa regulations, and their influence on cryptocurrency markets. Analysing stock market responses, we highlight significant shifts in liquidity, variance, and return dynamics post-MiCa-related announcements. Specifically, such announcements are associated with significant negative cryptocurrency returns and elevated liquidity. The findings reveal defined heterogeneity across different cryptocurrency sub-classes, each uniquely affected by its inherent attributes and susceptibility to regulatory changes. This work offers insights into the nature of market responses to regulatory intervention, providing an invaluable perspective on the equilibrium between cryptocurrency market behaviour and the evolving European regulatory landscape.